2014
DOI: 10.1016/j.atherosclerosis.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Small high-density lipoprotein is associated with monocyte subsets in stable coronary artery disease

Abstract: Objective: High-density lipoprotein (HDL) particles are heterogeneous in structure and function and the role of HDL subfractions in atherogenesis is not well understood. It has been suggested that small HDL may be dysfunctional in patients with coronary artery disease (CAD). Monocytes are considered to play a key role in atherosclerotic diseases. Circulating monocytes can be divided into three subtypes according to their surface expression of CD14 and CD16. Our aim was to examine whether monocyte subsets are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 47 publications
1
22
0
9
Order By: Relevance
“…Conversely, HDL-C has many athero-protective effects secondary to its reverse cholesterol transport, anti-inflammatory and antioxidant actions. Recent studies have shown a direct link between HDL and monocyte subgroups in patients with CAD and chronic renal disease [39][40][41]. In addition, HDL-C may impact the formation and activation of monocytes [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, HDL-C has many athero-protective effects secondary to its reverse cholesterol transport, anti-inflammatory and antioxidant actions. Recent studies have shown a direct link between HDL and monocyte subgroups in patients with CAD and chronic renal disease [39][40][41]. In addition, HDL-C may impact the formation and activation of monocytes [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Percentage of nonclassical monocytes is also positively associated with small HDL levels 73 . Nevertheless, the association between nonclassical monocytes and atherosclerosis does not necessarily imply causality.…”
Section: Atherosclerosismentioning
confidence: 99%
“…However, these properties varied in atherogenic dyslipidaemia, where small HDL particles were associated with the presence and severity of atherosclerotic disease. It was demonstrated that coronary artery disease (CAD) patients with elevated levels of small HDLs exhibited a shift towards pro‐inflammatory monocyte subset distribution as serum levels of small HDLs significantly correlated with the proportion of circulating non‐classical monocytes . The numbers of non‐classical monocytes were increased in hypercholesterolaemic patients with the ApoE4 allele as well as in healthy individuals with ApoE3/E4 or E4/E4 phenotype .…”
Section: The Role Of Monocytes In Atherosclerosismentioning
confidence: 99%